Effect of Temperature on Electrical Properties of Reduced Graphene Oxide (rGO)/Li-ion Embedded Flexible Solid Polymer Electrolyte Films. (2020) - Pandey, Mayank; Manoj, B.
Abstract: Reduced graphene oxide (rGO) was synthesized from graphite powder by modified Hummers method. The rGO is emerged with Polystyrene sulfonic acid/Lithium phosphate to prepare PL-rGO solid polymer electrolyte films. The electrical properties of Polystyrene sulfonic acid/Lithium phosphate/reduced graphene oxide composites were analyzed, which is an essential property to obtain the performance, reliability and lifetime of battery with respect to temperature. The mass and charge transfer process that takes place at the interface of electrode and electrolyte was obtained by Impedance analyzer. The Nyquist plots were plotted in the frequency range 1 Hz- 35 MHz at different temperatures (30-100 O C). The ionic conductivity of PL-rGO polymer electrolyte is 1.4x10 -3 S/c.m has been observed for the composition PSSA/Li3PO4/rGO::50:45:05 wt%. The conductivity of PL-rGO composites is directly related to temperature. The hopping of the ions in the PL-rGO is observed by using dc conductivity which follows the Arrhenius relationship